Robotic single-site secondary abdominal cerclage replacement following initial repair of cervical isthmus injury arising from a history of open abdominal cerclage and subsequent PPROM at 14 weeks gestation - Nurul Farhanah Binte Abdul Latif; Zhenkun Guan; Brooke Thigpen; Sowmya Sunkara; Xiaoming Guan (Intelligent Surgery, 2023)
Study objective: To demonstrate the surgical techniques for removal and replacement of a prior cerclage, repair of a cervical injury caused by the prior abdominal cerclage placement resulting in PPROM during surgery, and methods to mitigate the risk. Design: Stepwise demonstration with narrated video footage. Setting: An academic tertiary care hospital. Our patient is a 32-year-old G4P1 with a complex obstetric history. Her first pregnancy ended with a miscarriage at 7 weeks. A transvaginal cerclage was performed during her second pregnancy at 12 weeks, and she subsequently suffered from PPROM at 24 weeks. The baby was delivered via cesarean section and was 18 months old at the time of the last follow-up. Another transvaginal cerclage was performed at 14 weeks for her third pregnancy, which ended with an IUFD at 16 weeks. She subsequently underwent the removal of the vaginal cerclage and a D&C. In her fourth pregnancy, an open abdominal cerclage was attempted at 14 weeks of pregnancy. The latter caused PPROM during the surgery due to blind needle placement, which resulted in the loss of the fetus. Perioperative notes regarding that particular surgery were not accessible to us at the time of submission. She presented to us as a non-gravid patient seeking the replacement of her abdominal cerclage. Given a complex obstetric history of multiple second-trimester losses with two vaginal cerclages and one open abdominal cerclage, an abdominal cerclage was indicated at the level of the internal cervical os, regardless of cervical length, in a non-pregnant patient. Interventions: Cervical insufficiency is a condition that results in painless, recurrent pregnancy loss before the second trimester in the absence of biochemical triggers. Epidemiologically, cervical incompetence occurs in 0.1–1% of the obstetric population.1 Though rare, this condition has devastating consequences for both the expectant parents and the healthcare system, with preterm births responsible for 70% of all neonatal morbidity and mortality.2 The two most common surgical interventions aimed at resolving this condition are the transvaginal and abdominal cerclages. An abdominal cerclage has a reported success rate of 79–100% when done via laparoscopic means.3 This is the primary intervention indicated in patients with a history of failed transvaginal cerclages, a shortened or absent cervix due to cervical surgery, or uterine anomalies. Though the intervention has minimal risks and complications for the experienced surgeon in a non-gravid uterus, the difficulty exponentially increases post-conception and even more with increasing gestational age. Owing to the engorged uterine vessels during pregnancy and the amniotic sac that flanks the sides of the internal cervical os, the clearance for safe needle passage during cerclage placement is limited. This technical difficulty lends itself to causing the most common complication of abdominal cerclage: rupture of the membranes. PPROM accounts for 38% of all complications that arise during an abdominal cerclage placement4 and one of the gravest consequences is the subsequent loss of the fetus. Minimal advancement has been made in the standard techniques used to place the cerclage that would minimize the risk. Besides blind needle placement and its clear risks and ultrasound-guided technique,5,6 which would necessitate multiple specialists on hand, the surgeon suggests a trans-broad ligament approach. There is a case report by the same surgeon who performed it with great success.7 Essentially, the technique exposes the bilateral uterine vessels, which reduces the possibility of accidental damage to the arteries and eliminates the risk of blind needle placement piercing through the amniotic sac, leading to rupture of membranes and subsequent pregnancy loss.7 Multiple abdominal cerclages have been performed this way by the surgeon with a success rate of 100%; however, further research needs to be undertaken with greater power.We demonstrate three things in the video: a needleless technique to remove and replace a prior abdominal cerclage; a method to repair the internal cervical os after a cervical injury caused by the prior placement; and an abdominal cerclage placed months after the removal of the first, using standard technique. We performed all three procedures using a robotic-assisted single-site platform on a non-gravid patient.At the beginning of the surgery, the Mersilene tape from the prior abdominal cerclage was identified. The placement was regarded as being in the correct location, however it was loose circumferentially. Therefore, the decision was made to replace the tape in the same location with tighter banding. The needleless technique involved suturing the previous tape into the new one and using the prior tape to pull the new one through. This eliminated the need for another blind needle placement. However, a hysteroscopy done after the placement showed the tape within the uterine cavity. The surgeon initiated the removal of the recently placed cerclage. During the creation of the bladder flap, a 2 cm defect at the level of the internal os at the location of the prior cerclage was noted. This gaping defect left the Rumi manipulator visible and extended laterally into the broad ligament. A mutual decision was made by the surgeon and the patient's husband to repair the uterine defect during the present surgery and defer the cerclage placement to a later date. The first surgery was completed after a hysteroscopy was done, and no sutures were visualized within the uterine cavity. Five months later, the patient followed up for her abdominal cerclage placement. A preliminary hysteroscopy noted a well-healed uterine cavity. Therefore, an abdominal cerclage was placed via a robotic-assisted platform using the blind needle technique. A concluding hysteroscopy and view in fire-fly mode demonstrated no Mersilene tape or sutures within the internal cervical os. There were no complications during either surgery, and the patient was discharged on the same day for both. Conclusion: Removal and replacement of prior cerclage can be done needleless under the correct conditions. For patients referred following a failed transabdominal cerclage especially due to intraoperative cervical injury, the surgeon recommends a preliminary hysteroscopy to determine the extent of damage and prevent redundant effort. Blind needle placement remains the most standard technique in performing abdominal cerclage, yet it is one of the highest cause of complications in the surgical intervention. The repair and replacement of the cerclage were necessitated in this case after the prior surgeon had impaled the amniotic sac during blind needle placement, resulting in the loss of the fetus. Currently, the trans-broad ligament approach offers a feasible and simple technique for surgeons seeking to reduce risks, although further research is needed.